Redesign UI/UX Aplikasi Mobile Sikuat Menggunakan Metode User Centered Design (UCD) - Figo Stevhen Hidayat; Made Agung Raharja (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
SIKUAT is an application/platform developed to be an information system that manages and disseminates information related to health centers in Sidoarjo. Based on observations made on the features owned by the SIKUAT application, reviews on the Play Store, and also interviews conducted with 5 users of the application. It was found that there were problems in the UI (User Interface) and UX (User Experience) aspects of the SIKUAT mobile application. The problems faced in the SIKUAT mobile application include typography, layout, lack of navigation, and lack of something interesting for users to linger in the system. Therefore, this study will apply the usercentered design method which begins with the process of understanding the context of use to meet human-based needs (user-centered), which aims to create something new based on user needs. The results of this study will produce a prototype of the SIKUAT application that has been re-engineered (redesigned). Furthermore, the prototype was tested using the System Usability Scale (SUS) method and obtained an average SUS value of 82.5. From the results of this test, it can be concluded that the redesign of the SIKUAT application has been successful and well received by users, because it meets the acceptable feasibility criteria.